EGF signaling promotes the lineage conversion of astrocytes into oligodendrocytes - Xinyu Liu; Conghui Li; Jiao Li; Lesi Xie; Zeng Hong; Kang Zheng; Xiaofeng Zhao; Aifen Yang; Xiaofeng Xu; Huaping Tao; Mengsheng Qiu; Junlin Yang (BMC, 2022)
Abstract Background The conversion of astrocytes activated by nerve injuries to oligodendrocytes is not only beneficial to axonal remyelination, but also helpful for reversal of glial scar. Recent studies have shown that pathological niche promoted the Sox10-mediated astrocytic transdifferentiation to oligodendrocytes. The extracellular factors underlying the cell fate switching are not known. Methods Astrocytes were obtained from mouse spinal cord dissociation culture and purified by differential adherent properties. The lineage conversion of astrocytes into oligodendrocyte lineage cells was carried out by Sox10-expressing virus infection both in vitro and in vivo, meanwhile, epidermal growth factor (EGF) and epidermal growth factor receptor (EGFR) inhibitor Gefitinib were adopted to investigate the function of EGF signaling in this fate transition process. Pharmacological inhibition analyses were performed to examine the pathway connecting the EGF with the expression of oligodendrogenic genes and cell fate transdifferentiation. Results EGF treatment facilitated the Sox10-induced transformation of astrocytes to O4+ induced oligodendrocyte precursor cells (iOPCs) in vitro. The transdifferentiation of astrocytes to iOPCs went through two distinct but interconnected processes: (1) dedifferentiation of astrocytes to astrocyte precursor cells (APCs); (2) transformation of APCs to iOPCs, EGF signaling was involved in both processes. And EGF triggered astrocytes to express oligodendrogenic genes Olig1 and Olig2 by activating extracellular signal-regulated kinase 1 and 2 (Erk1/2) pathway. In addition, we discovered that EGF can enhance astrocyte transdifferentiation in injured spinal cord tissues. Conclusions These findings provide strong evidence that EGF facilitates the transdifferentiation of astrocytes to oligodendrocytes, and suggest that targeting the EGF-EGFR-Erk1/2 signaling axis may represent a novel therapeutic strategy for myelin repair in injured central nervous system (CNS) tissues.